The concentration of humic substances and their contribution to iron speciation in waters of the Atlantic sector of the Arctic Ocean and the North Atlantic Ocean - Luis Miguel Laglera; Camila Fiaux Sukekava; Rob Middag; Loes Gerringa; Hans A Slagter; Rebecca Zitoun; Wen-Hsuan Liao; Micha J A Rijkenberg (PANGAEA, 2025)
In this dataset, we present findings on concentrations (< 0.2 μm) of humic substances, dissolved iron, and humic iron (the fraction of dissolved iron complexed by humic substances) in samples gathered during three distinct cruises across the North Atlantic and Arctic oceans. Our objective was to track the migration of humic substances originating from Siberian river outflows, as they traverse from surface waters of the Arctic Ocean into the North Atlantic Ocean, and to understand their impact on dissolved iron transport in the region. The dataset encompasses results from three cruises: the TransArcII expedition aboard the RV Polarstern (PS94) in the central basins and Atlantic sector of the Arctic Ocean, the GN05 expedition (PS100) in waters of the Fram Strait, and the Metalgate expedition aboard the RV Pelagia (64PE474) in waters surrounding Iceland. Dissolved iron concentrations were determined using ICP-MS (Middag et al. 2023), while humic substances and iron bound to humic substances were measured via Adsorptive Cathodic Stripping Voltammetry following the method outlined by Sukekava et al. (2018). Our findings reveal significant regional variations in the role of humic substances, influencing the prevention of dissolved iron precipitation and facilitating its transport. Middag, R., R. Zitoun, and T. Conway, Trace Metals, in Marine Analytical Chemistry, J. Blasco and A. Tovar-Sánchez, Editors. 2023, Springer International Publishing: Cham. p. 103-198. Sukekava, C., et al., Determination of the contribution of humic substances to iron complexation in seawater by catalytic cathodic stripping voltammetry. Talanta, 2018. 189: p. 359-364.